Liquefaction/solubilization of low-rank Turkish coals by white-rot fungus (Phanerochaete chrysosporium) - Elbeyli, Iffet Yakar; Palantoeken, Arzu; Piskin, Sabriye; Kuzu, Huriye; Peksel, Ayseguel (TAYLOR & FRANCIS INC, 2006)
Microbial coal liquefaction/solubilization of three low-rank Turkish coals (Bursa-Kestelek, Kutahya-Seyitomer and Mugla-Yatagan lignite) was attempted by using a white-rot fungus (Phanerochaete chrysosporium DSM No. 6909); chemical compositions of the products were investigated. The lignite samples were oxidized by nitric acid under moderate conditions and then oxidized samples were placed on the agar medium of Phanerochaete chrysosporium. FTIR spectra of raw lignites, oxidized lignites and liquid products were recorded, and the acetone-soluble fractions of these samples were identified by GC-MS technique. Results show that the fungus affects the nitro and carboxyl/carbonyl groups in oxidized lignite sample, the liquid products obtained by microbial effects are the mixture of water-soluble compounds, and show limited organic solubility.
Keywords: low-rank coal; white-rot fungus; liquefaction/solubilization; HUMIC ACIDS; BROWN-COAL; SOLUBILIZATION; SPECTROSCOPY; DEGRADATION; LIGNITES; ATTACK; Energy & Fuels; Engineering; Environmental Sciences & Ecology